Efficacy of photodynamic therapy in the treatment of venous trophic ulcers: results from the experiment - B. V. Boldin; P. Yu. Turkin; A. P. Oettinger; V. Yu. Bogachev; N. O. Somov; S. G. Kuzmin; V. B. Loschenov; L. M. Mikhaleva; K. Yu. Midiber (Амбулаторная хирургия)
Introduction. Today, antimicrobial photodynamic therapy (a-PDT) becomes more and more popular, because of it pronounced bactericidal activity, anti-inflammatory effect. At the same time, no animal model studies have been conducted on morphological changes in cells after exposure to PDT on venous ulcers (VU) when using different types of photosensitizers (PS). The problem of comparing morphological changes in tissues when using a-PDT vs conventional PDT have not yet been resolved.Aim. Evaluation of the effectiveness of PDT and APDT in a comprehensive examination of trophic ulcers in an in vivo experiment and compare them with standard methods for the treatment of VLU.Materials and мethods. A series of experiments was conducted on 21 rabbits, separated into 3 equal groups of 7 rabbits each. Venous trophic ulcer was originally modeled for all rabbits. To obtain a VU, we performed an additional ligation of v. femoralis. The control group received standard therapy for VU. The PDT group had PDT with Photosens. The a-PDT group underwent a-PDT using Cholosens. Every 3 days, picture of local inflammation, regeneration rate and ulcer volume were determined. A morphological study of VLU was carried out on the first, 9th and 15th days.Results. The a-PDT group, day 15: 100% wound epithelization. Control group, day 21st: The volume of wounds decreased on average by 50%. The PDT group: 100% wound epithelization. The morphological study indicated a positive trend in the a-PDT group compared with PDT and control groups, which resulted in a decrease in the total mass of necrotic detritus, a change in the quantitative and qualitative composition of inflammatory infiltrate.Conclusion. The data obtained indicate that the use of a-PDT is recommended in treatment of VLU. Both PDT and a-PDT methods showed better results in comparison with standard therapy.